Posterior interosseous nerve palsy after closed proximal forearm fractures. (October 2019) - Bulstra, L.F.; Schep, N.W.L.; van der Vlies, C.H.
Abstract: Although rare, posterior interosseous nerve (PIN) palsy can occur in patients with a closed proximal forearm fracture and may present in a delayed fashion after initial trauma. In this case series, three cases of posterior interosseous nerve (PIN) injury following proximal forearm fractures are presented and discussed. Our literature search yielded six studies concerning PIN injury in radial head/neck fractures and proximal forearm fractures. Out of a total of 8 patients, 7 patients were treated non-operatively and in one patient a PIN release was performed. One patient was lost to follow-up, all other 7 patients showed successful recovery. A treatment algorithm for PIN palsy after proximal forearm fractures is provided. Based on our experience and what we found in literature, it seems safe to treat PIN palsies conservatively.